Pragmatismo e esfera pública : um diálogo entre Richard Rorty e Jürgen Habermas - Sousa Neto, Helson de (2012)
Jürgen Habermas, while addressing the pragmatic theory, tried to solve problems in his Public Sphere Structural Change work (1962). Therefore, our overall goal is to advance with studies that will contribute to the continuity of the program proposed by Habermas\'s linguistic sudden turn as well as for the understanding of his debate with Richard Rorty of the themes \"truth and justification.\" Our initial concern was to relay on classical pragmatism represented by Charles Sanders Peirce, William James and John Dewey on contemporary pragmatism, which give support to our work, since Jürgen Habermas and Richard Rorty resort to according to their own way - these two phases of a traditional American thinking to develop their work. Since the pragmatism arises with the proposal to try to overcome the insufficiency of metaphysics and epistemology, Habermas and Rorty lean on the pragmatism to carry out the sudden turn, we tried to consider the criticism that Habermas and Rorty make of the representational view of knowledge and truth that the metaphysics and epistemology suggest. After all, these two classical schools represent the core of the discussion about what is true and what is justified. As a result of this discussion we observed that Habermas and Rorty converge to the proposal that the linguistic expression is the means by which the representation and knowledge happen, and that the truth can only be justified rationally and not on the origin of representations as metaphysics and epistemology present .On one hand Habermas and Rorty agree on this point, on the other hand both disagree over the issue of truth. For Habermas, it is necessary that truth and reason work together; however, according to Rorty, this journey is useless, since something that is true does not need to be justified or if something is well justified does not mean that justification implies that something is true. The core of that debate has its origin in the use of cautionary truth predicate. Thus, our goal is to understand why these differences occur, that is, why Habermas agrees while Rorty does not. Within the discussion of truth and justification Habermas innovates when he proposes the \"ideal model of speech.\" In such case, we seek to highlight what is this model and how it contributes to the consensus about truth and justification, and what interpretations Rorty makes of this concept. Finally, as Habermas believes that the relationship between truth and justification is a relationship of language practices, our challenge was to understand how this issue as well as its proposal for a pragmatic sudden turn improves the understanding of the concept of public sphere at the same time that it is an effort to solve the problems it presents.